Development of a Ni-CaO-mayenite combined sorbent-catalyst material for multicycle sorption enhanced steam methane reforming. (15th December 2018) - Di Giuliano, A.; Giancaterino, F.; Courson, C.; Foscolo, P.U.; Gallucci, K.
Graphical abstract: Highlights: Synthesis and characterization of an optimized combined sorbent-catalyst material. Successful multicycle SESMR/regeneration test (205 cycles, 15 days non-stop). High stability of both catalytic and sorption functions. Abstract: This paper deals with a Ni-CaO-mayenite combined sorbent-catalyst material (CSCM) for sorption enhanced steam methane reforming (SESMR), with Ni and CaO fractions optimized for a multicycle SESMR/sorbent regeneration process (10 wt% and 13.5 wt% respectively). The CSCM was purposely synthesized by wet mixing followed by wet impregnation. Used characterization methods were XRD, BET and BJH methods, SEM/EDS, STEM/EDS, TPR, TGA. The CSCM reactivity was checked by a 3 h reforming test in a microreactor. The material was then subjected to two hundred and five SESMR/regeneration cycles utilizing a fully automated bench scale rig with a packed bed reformer/calciner reactor: a very stable and satisfactory performance was observed, without decline of Ni catalytic activity and CO2 sorption capacity over a 15 days no-stop test. This stability towards multicycle operation was confirmed by after-test characterizations.